Strategi Pemasaran Madu yang Berasal dari Lebah Hutan (Apis dorsata) di Kabupaten Timor Tengah Selatan (Studi Kasus di Desa Loli dan Desa Fatumnasi) - Samuel Abraham Ayub Meko; Johanna Suek; Norman P. L. B. Riwu Kaho; Nixon Rammang (Wana Lestari, 2026)
The purpose of this research is for the marketing strategy of forest honey bees (Apis dorsata) in South Central Timor Regency. This research was conducted with a purposive method. The data obtained is in the form of honey consumer segmentation analysis using descriptive analysis, then the data is analyzed using SWOT. The tool used to compile strategic factors using the SWOT matrix. The results of the marketing channel for wild bee honey in Loli Village and Fatumnasi Village have three marketing channels, namely the first channel with 0 margin and 100% farmer share. The second channel has a margin of IDR 35,000 and a farmer share of 80%. The third channel has a margin of IDR 120,000 and a farmer share of 53.84%. Strengths (S), namely honey is a superior HHBK, harvested traditionally, original honey quality, honey price is relatively cheap, strategic marketing location, has a community network group, honey has many health benefits. Weaknesses (W) are traditional processing techniques, have not carried out maximum promotion, have low human resources, packaging is not sterile, product packaging is less attractive, and harvest is not sustainable. Opportunity (O) namely healthy lifestyle changes, consumers who become agents, demand for honey is quite high, media promotion is young. Threats (T) are low level of trust, competitors in the same field, honey prices vary, honey quality is influenced by nature, some nest trees are located in nature reserve areas, forest and land fires, and deforestation. The strategy that can be taken to develop honey marketing is the S-T (Strengths-Threat) strategy, namely the category of honey as a superior HHBK, it is necessary to maintain the quality of honey so that the level of consumer confidence in genuine honey increases, the existence of community network groups with relatively cheap sales makes competitors in the same field , honey is a superior HHBK so it is necessary to maintain the availability of honey which is influenced by nature.